The outcome and risk factors associated with central and peripheral nervous system involvement in hospitalized COVID-19 patients: a retrospective cohort study - Hanganu, Andreea Raluca; Niculae, Cristian-Mihail; Dulămea, Adriana Octaviana; Moisă, Emanuel; Constantin, Rareș; Neagu, Georgiana; Hristea, Adriana (Frontiers in Neurology, 2024)
Introduction SARS-CoV-2 infection can affect any organ, including both the central nervous system (CNS) and peripheral nervous system (PNS). The aim of this study was to explore the outcome and risk factors associated with the involvement of either CNS or PNS in a cohort of hospitalized COVID-19 patients. Methods We performed a retrospective observational cohort study of hospitalized adult patients with COVID-19, between May 2020 and December 2022, presenting with new onset neurological disabilities any time after admission. Results We included 115 patients, 72 with CNS manifestations and 43 with PNS involvement. The CNS manifestations were COVID-19-associated encephalopathy, headache, neurovascular events, and seizures in 80.5, 43, 31.9, and 11.1% of patients, respectively. The neurovascular events were ischemic stroke in 17 (23.6%) patients, hemorrhagic stroke in 6 (8.3%) patients, venous thrombosis in 1 (1.4%) patient, and subarachnoid hemorrhage in 1 (1.4%) patient. Cranial nerve involvement was the most frequent PNS manifestation in 34 (79%) cases, followed by mononeuritis in 5 (11.6%) patients and polyneuropathy in 4 (9.3%) patients. The affected cranial nerves were the vestibulocochlear nerve in 26 (60.5%) patients, the olfactory nerve in 24 (55.8%) patients, the oculomotor nerves in 5 (11.6%) patients, and the facial nerve in 1 (2.3%) patient. Two patients (9.3%) presented with polyneuritis cranialis. Older age (HR = 1.02, 95% CI: 1.003–1.037, p = 0.01), COVID severity (HR = 2.53, 95% CI: 1.42–4.5, p = 0.002), ischemic cardiac disease (HR = 2.42, 95% CI: 1.05–5.6, p = 0.03), and increased D-dimers (HR = 1.00, 95% CI: 1.00–1.00, p = 0.02) were independently associated with the development of CNS manifestations. The factors associated with in-hospital mortality were age (HR = 1.059, 95% CI: 1.024–1.096, p = 0.001), C-reactive protein (HR = 1.006, 95% CI: 1.00–1.011, p = 0.03), CNS involvement (HR = 9.155, 95% CI: 1.185–70.74, p = 0.03), and leucocyte number (HR = 1.053, 95% CI: 1.026–1.081, p < 0.001). Conclusion COVID-19-associated encephalopathy was the most common CNS manifestation in our study, but neurovascular events are also important considering the overlap between inflammatory and prothrombotic pathways, especially in severe cases. CNS involvement was associated with in-hospital all-cause mortality. PNS findings were various, involving mostly the cranial nerves, especially the vestibulocochlear nerve.